Figure-Ground Analysis of The Pinisi Village Area in Balikpapan City - Putra, Rulliannor Syah; Rahman, Rizky Nur; Azizah, Vita Ovie Anggraeni; Aolia, Siti Maisura (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2026)
Abstract. Pinisi Village and its surroundings are coastal areas that have unique characteristics in terms of accessibility, spatial patterns, and the cultural and social activities of their residents. This study aims to analyze the integration between circulation path elements, spatial patterns, and local culture in order to understand the connection between building mass and open space. The methods used include field observation (field research) to identify the character of the space and social activities, land mapping analysis to examine the relationship between building mass and open space, and literature studies from city planning regulations and related journals. The results of the study show that the circulation paths in this area are dominated by narrow roads that are more suitable for pedestrians and small vehicles, but are still poorly integrated with the main public space. The spatial patterns formed are organic, with an uneven distribution of open space, but remain the center of social activities for the community. The analysis shows that open space plays an important role in maintaining the social life of coastal communities. The conclusion of this study indicates the need for re-planning of circulation paths to improve regional integration and optimize open space to strengthen the social and cultural identity of coastal communities.